Here's the question you clicked on:
Pie_Boi
factor x^6-64
Difference of two squares: a^2 - b^2 = (a + b)(a - b) Difference of two cubes: a^3 - b^3 = (a - b)(a^2 + ab + b^2) Sum of two cubes: a^3 + b^3 = (a + b)(a^2 - ab + b^2) x^6 - 64 (factor as difference of two squares) (x^3 + 8)(x^3 - 8) (factor first group as sum of two cubes) (x + 2)(x^2 + 2x + 4)(x^3 - 8) (factor third group as difference of two cubes) (x + 2)(x^2 - 2x + 4)(x - 2)(x^2 + 2x + 4) (x + 2)(x - 2)(x^2 + 2x + 4)(x^2 - 2x + 4) <===ANSWER